Ethnobotanical study in a rural settlement in Amazon: contribution of local knowledge to public health policies (Research, Society and Development, 2022)
Medicinal plants continue to be appropriate and preferred alternatives for primary health care among rural Amazon populations, although their incorporation into conventional health services has been slow and challenging. Besides that, few Amazon plants have been considered in current public health policies. We sought here to better understand the role of medicinal plants in the therapeutic practices of residents of the Paulo Fonteles Land Settlement at Mosqueiro, a district within Belém (Pará State, Brazil) and identify species of potential value for government health services. Ethnobotanical data was obtained through semi-structured interviews with 61 residents. Results were analyzed using indices of use-report (Ur) and by consulting official documents of the Brazilian Ministry of Health (MS). The settlers use at least 61 exotic plants and 67 natives to Brazil; of the latter species, 21 were endemic to the Amazon region. The medicinal plants cited by the settlers were used for treating 76 symptoms and/or illnesses, especially related to digestive, respiratory, dermatological, and women's health problems; Anacardium occidentale, Alternanthera brasiliana, and Dalbergia monetaria had the highest URs. Forty plants are cited in MS documents. This research incentive more studies with Amazonian species and shows a list of 11 species for inclusion in health services offered to local populations.